FACTORS RELATING TO THE UTILIZATION OF NCD INTEGRATED POST: Utilization of NCD Integrated Post - Erwin Azizi Jayadipraja; Putu Suri Saraswati; Sartini Risky; Hadafiah Hadafiah; Sunarsih Sunarsih (STIKes Mandala Waluya Kendari, 2020)
Background: Indonesia has the highest prevalence of Non-Communicable Disease (NCD)in 2013. NCD which is always listed in the top 10 diseases in Southeast Sulawesi is hypertension and diabetes mellitus. NCD Integrated Post is an effort to detect and overcome the early presence of NCD threat factors. However, there has been a decrease in the prevalence of integrated post visits from 2017 to 2018 at the Barangka Public Health Centre. The purpose of this study was to analyze the utilization of NCD Integrated Post in the work area of ??Barangka Health Centre in Buton Regency. Methods: This type of research uses a cross-sectional study design. This study was conducted from November to December 2019. The population in this study were all people in the work area of ??Barangka Health Centre, Buton Regency in 2018 with ages> 15 to 59 years, namely 3,584 people. The number of the samples was 134 respondents. A questionnaire was used as the method of data collection. Results: The results showed that the chi square of cadre support X2 count =36,460> X2 table value = 3,841 and health status is X2 count = 32,308> table X2 value = 3,841. Therefore, all variables are influencing the utilization of NCD Integrated Post. Conclusion: Health status and cadre influenced significantly the community in utilizing NCD Integrated Post at the Barangka Health Centre in Buton Regency.